Impact of Hairdin, Miro Khan and Shahdad Kot Drainage on Hamal Dhand, Sindh - Mahessar, A. A.; Qureshi, A. L.; Laghari, A. N.; Qureshi, S.; Shah, S. F.; Shaikh, F. A. (Engineering, Technology & Applied Science Research, 2018)
Safe drinking water is a basic need. Surface water bodies are the primary source of safe water. Drain water, industries, urban/rural effluents, and waste materials are often disposed into surface water bodies without any treatment. All major water bodies of Sindh province are thus more or less polluted. These water bodies are interconnected with the Indus River like the artery system for blood circulation in bodies of living things. The main source of contamination of Hamal Lake is the disposal of the effluents of Hairdin drain, Miro Khan drain, and Shahdad Kot drain. This lake’s main source of fresh water is rained from Khirthar mountains. Hamal lake is connected through the Main Nara Valley drain (MNVD) to Manchar lake that eventually outfalls into Indus River. Hence, drain water pollutes not only Hamal and Manchar lakes but also Indus River due to their interconnection. Presently, right bank outfall drains (RBOD I-III) have been constructed for safe disposal of drain effluents thus avoiding the polluting of freshwater bodies.